Covid-19 lessons (2020)
The confinement of the world has brought important teachings. Although pandemics of the past such as smallpox, black plague or the Spanish flu caused a greater number of deaths, an element in the 21st century makes it play an essential role in viral containment: information. According to this statement, the permanent monitoring of the John Hopkins University, the immediate news about the number of deaths, infected and recovered, almost in real time, shows that today the attack can be controlled. In this regard it can be seen that: China opened Wuhan, where the coronavirus was born. He had three months of draconian measures. And today zero dead. Of course, the sub-registers are worrisome, as well as the asymptomatic cases.